Review of Hadith in Marriage Agreements and Its Perspective in Indonesian Positive Law - Nurwahyudin, Dindin Syarief (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Marriage agreements are legal instruments that play a role in regulating the rights and obligations of couples, especially related to property rights, both from the perspective of Islamic law and positive law in Indonesia. This study departs from the urgency of low understanding and application of marriage agreements in society due to social stigma and lack of legal literacy. The formulation of the problem in this study includes how to reconstruct the legality of mixed marriage agreements and their implications for property rights from the perspective of Islamic law and positive law. This study uses an empirical legal method with a qualitative descriptive approach. Primary data were obtained through interviews with informants, while secondary data were obtained from literature studies of applicable legal regulations and studies of hadiths related to marriage agreements. The analysis was carried out using the deductive method and the maqashid sharia approach to understand the relevance of marriage agreements in the context of Islamic law. The results of the study indicate that marriage agreements have a strategic role in providing legal certainty, asset protection, and regulating the rights and obligations of couples, especially in cases of polygamy, divorce, and inheritance. However, the application of this agreement is still limited due to cultural factors and negative perceptions in society. In Islamic law, a marriage contract is permitted as long as it does not conflict with sharia principles, while in positive law it is recognized and has legal implications for the management of joint assets and the financial rights of couples. In conclusion, a marriage contract acts as a legal instrument that can improve the welfare of couples by providing protection for property rights. Therefore, further socialization and an active role from legal and religious authorities are needed to increase public understanding of the benefits of this agreement in building a harmonious and just family.